Bacterial Detection and Recovery From Poultry Litter - Plumblee Lawrence, Jodie R.; Cudnik, Denice; Oladeinde, Adelumola (Frontiers in Microbiology, 2022)
The level of pathogens in poultry litter used for raising broiler chickens is critical to the overall health of a broiler chicken flock and food safety. Therefore, it is imperative that methods used for determining bacterial concentration in litter is accurate and reproducible across studies. In this perspective, we discuss the shortcomings associated with current methods used for bacterial quantification and detection from litter and assess the efficacy of one method for pathogen and commensal (Campylobacter, Salmonella, Escherichia coli (E. coli) and Enterococcus spp.) recovery. The limit of quantification and detection for this method differed between pathogens and the recovery rate (~138-208%) was higher for Salmonella, E. coli and Enterococcus compared to Campylobacter (24%). Our results suggest that pathogen recovery from litter is highly variable and pathogen concentrations need to be reported in dry weight before comparisons can be made between studies.